Assessing the Solvency, Underwriting Risk and Profitability of the Kenyan Insurance Sector: Array - Morara, Kamanda; Sibindi, Athenia Bongani (Acta Universitatis Danubius. Œconomica, 2021)
The aim of this study was to assess the solvency, underwriting risk and financial performance of the Kenyan insurance industry. The insurance industry is a key player that drives economic growth in Kenya. Notwithstanding there has been a dearth of studies that have investigated the factors that have a bearing on the financial performance and by extension the financial stability of the Kenyan insurance sector. In this article, we explored how solvency and underwriting risk impacted on the financial performance of insurance firms in Kenya for the period 2009 to 2018. We employed descriptive statistics and correlational analysis to analyse the data. The sourced secondary data from the Insurance Regulatory Authority Annual Reports. There were two main findings from this study. Firstly, it was established that solvency position of Kenyan insurance companies has been increasing steadily over the years. Solvency was also found to be positively correlated to financial performance. Secondly, it was found that underwriting risk was on an upward trend. Further it was established that underwriting risk proxied by the combined ratio was positively associated with the financial performance variable. This study therefore makes a contribution to the sparse literature on the financial performance of the insurance sector in Kenya. Furthermore, it provides pointers to the management insurance companies on the aspects of their business that would need greater attention to drive and sustain superior financial performance.